2015
DOI: 10.1186/s40494-015-0058-x
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic use of Py–THM–GCMS, DTMS, and ESI–MS for the characterization of the organic fraction of modern enamel paints

Abstract: Introduction:In this study, mass spectrometric techniques (THM-Py-GCMS, DTMS and ESI-MS) have been used to characterize the organic fraction of early twentieth century oil-based enamel paints. Analysis has been carried out on dry and liquid samples from historical reference paints, and on color swatches from commercial paint brochures, with a special focus on Ripolin. This renowned French brand of enamel paints, manufactured for household and other uses since 1897, was reportedly used by many avant-garde artis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…8a-e) [28]. A differentiation between oil house paints and artists' oil tubes would be of interest in this context, but is not achievable by FTIR spectroscopy and requires micro-destructive mass spectrometry analysis [29]. As a preliminary step oriented to guide the sampling campaign, non-invasive FTIR spectroscopy enabled us to roughly classify Alchemy's oil-based paints considering signals from additives, alteration products or, more loosely, the entire spectral profile in combination with the visual differences in term of texture, body, and type application of the paints.…”
Section: Characterization Of Binding Mediamentioning
confidence: 99%
“…8a-e) [28]. A differentiation between oil house paints and artists' oil tubes would be of interest in this context, but is not achievable by FTIR spectroscopy and requires micro-destructive mass spectrometry analysis [29]. As a preliminary step oriented to guide the sampling campaign, non-invasive FTIR spectroscopy enabled us to roughly classify Alchemy's oil-based paints considering signals from additives, alteration products or, more loosely, the entire spectral profile in combination with the visual differences in term of texture, body, and type application of the paints.…”
Section: Characterization Of Binding Mediamentioning
confidence: 99%
“…4) (Kokkori et al 2013) a practice also described in the literature (Horton Sabin 1904;Uebele 1913;Cruickshank 1915). Castor oil was identified only in two samples of red Ripolin paint pigmented with alizarin; the identification of other types of drying oil such as soybean, perilla or fish oil recommended in the technical literature was not possible because of the lack of specific chemical markers for these materials.…”
Section: Binders and Resinsmentioning
confidence: 88%
“…On the other hand, preliminary analyses of binding media in artists' tube paints carried out for this study suggested a higher degree of variability in formulations with respect to oil types and additives. The organic components of the Ripolin and tube paints will be discussed in more detail in separate papers (Kokkori et al 2013(Kokkori et al (in preparation), 2014.…”
Section: Binders and Resinsmentioning
confidence: 99%
“…In einer umfassenden Studie von Kokkori und Mitarbeitern wurden THM/Py‐GC/MS, DTMS und Elektronenspray‐Ionisation‐MS (ESI‐MS) zur Charakterisierung der organischen Bestandteile von Öl‐basierten Enamel‐Farben des frühen 20. Jahrhunderts benutzt.…”
Section: Von De‐ms Und Dtms Zu Ega‐msunclassified